INVESTIGATION OF DIFFERENT WAYS OF REDUCING THE OXYGEN REQUIREMENT OF YEAST - Permyakova L.V. (Техника и технология пищевых производств)
Oxygen is an important component of the yeast cultivation medium and it is necessary for the synthesis of sterols and unsaturated fatty acids that make up the membrane. The shortage of these lipid compounds or oxygen in the medium leads to culture degeneration. The provision of yeast culture with atmospheric oxygen can be achieved by aeration of the wort or the inoculum before their introduction into the fermentation medium. The article deals with various ways of providing brewers’ yeast with oxygen and reducing the need of the culture for anaerobic growth factors. It is shown that the inoculum pre-fermentation treatment in green (new) beer (1: 2) by brief aeration (30-40 min) followed by storing without air access for 2-4 hours enables yeast to synthesize a sufficient amount of sterols and, at the same time, to maintain high fermentation activity. It has a positive effect on the biomass reproduction and extracts decrease. The use of the yeast aeration has significant advantages over the wort aeration, since it enables to obtain beer with better organoleptic properties alongside with power reduction (approximately 60 times). These data have been confirmed at one of the breweries in the Kemerovo region. The effect of reducing the oxygen requirement of the yeast culture is maintained during two generations and increases when using strains with high requirement for this component. It is possible to reduce the oxygen requirement of microbial cells due to the enrichment of the fermentation medium with sterols and unsaturated fatty acids by introducing a specially prepared yeast autolysate. The peculiarity of its production is the preaeration of the yeast suspension with compressed air followed by autolysis. This contributes to the increase of anaerobic growth factors in the cell biomass.